Biopharmaceutical raw material variation and control. (December 2018) - Dickens, Jason; Khattak, Sarwat; Matthews, Thomas E; Kolwyck, Dave; Wiltberger, Kelly
Abstract : The current paradigm for raw material control in the biopharmaceutical industry remains a combination of compendial tests, function-based test and engineering controls. Moreover, ad hoc scale-down process studies remain the de facto approach to understand raw material variation challenges. The biopharmaceutical industry, however, continues to experience the impact of raw material variation are current approaches are insufficient to assess key raw material attributes. Here we review the current state of raw material variation and its biopharmaceutical impact along with analytical methods optimized for raw material characterization. A systematic raw material characterization and control strategy is then outlined as an integrated approach to address cell culture raw material variation challenges. This comprehensive long-term approach can be applied throughout the biopharmaceutical manufacturing process and across further modalities such as small molecules, proteins, and other cellular therapies.